Design of an Arduino Mega-Based Walking Cane Assistive Device to Improve the Quality of Life for the Elderly in the Riau Islands Province - Dimas Akmarul Putera; Aulia Agung Dermawan; Dwi Ely Kurniawan; Alvendo Wahyu Aranski; Rafi Dio (Universitas Negeri Semarang, 2023)
Purpose: The number of people aged 60 or older is expected to increase globally by nearly three times from 737 million in 2009 to 2 million by 2050. Indonesia's population is projected to reach 28 million by 2045, making up nearly one-third of the total population. In 2020, the population aged 60 or older reached 29.52 million, with 29.52 million from the last two houses being occupied by a house due to numerous housing programs that require a close relationship between people. The study suggests that a house with a strong sense of belonging is a risky group required attention. The study uses a smartphone with a 180° panorama camera and GPS to help locating the house and performing its activities.Methods: Anthropometry can be defined as the study of body dimensions, namely body size, shape, strength and work capacity for the purpose of body design and composition and prototyping. Results: This research has resulted in elderly sticks that use sensors to help elderly mobility. This stick can detect the environment nearby the ESP32-Cam with the password